Population pharmacokinetics and dose rationale for aciclovir in term and pre‐term neonates with herpes - S. D'Agate; D. Ruiz Gabarre; O. Della Pasqua (Wiley, 2024)
Abstract Aciclovir is considered the first‐line treatment against Herpes simplex virus (HSV) infections in new‐borns and infants. As renal excretion is the major route of elimination, in renally‐impaired patients, aciclovir doses are adjusted according to the degree of impairment. However, limited attention has been given to the implications of immature renal function or dysfunction due to the viral disease itself. The aim of this investigation was to characterize the pharmacokinetics of aciclovir taking into account maturation and disease processes in the neonatal population. Pharmacokinetic data obtained from 2 previously published clinical trials (n = 28) were analyzed using a nonlinear mixed effects modeling approach. Post‐menstrual age (PMA) and creatinine clearance (CLCR) were assessed as descriptors of maturation and renal function. Simulation scenarios were also implemented to illustrate the use of pharmacokinetic data to extrapolate efficacy from adults. Aciclovir pharmacokinetics was described by a one‐compartment model with first‐order elimination. Body weight and diagnosis (systemic infection) were statistically significant covariates on the volume of distribution, whereas body weight, CLCR and PMA had a significant effect on clearance. Median clearance varied from 0.2 to 1.0 L/h in subjects with PMA <34 or ≥34 weeks, respectively. Population estimate for volume of distribution was 1.93 L with systemic infection increasing this value by almost 3‐fold (2.67 times higher). A suitable model parameterization was identified, which discriminates the effects of developmental growth, maturation, and organ function. Exposure to aciclovir was found to increase with decreasing PMA and renal function (CLCR), suggesting different dosing requirement for pre‐term neonates.